Pemanfaatan financial technology dan aplikasi smartphone dalam meningkatkan usaha mikro dan kecil pada era pandemi covid-19 di Kelurahan Mustikajaya - Soeharjoto Soekapdjo; Syofriza Syofyan; Bahtiar Usman; Lydia Rosintan Simanjuntak; Debbie Aryani Tribudhi (ABDIMAS DEWANTARA, 2022)
The Covid-19 pandemic had an impact on health which ultimately resulted in major changes in consumption behavior and industrial revolution 4.0 acceleration, thus lowering people's incomes. Purpose of this community service is to improve micro and small businesses in facing economic impact of the Covid-19 pandemic in Mustikajaya Village. Community service team provides education and training in financial technology and optimizes utilization of  applications on smartphones. This activity, improving partners knowledge and insights to the source of funds, financial administration, production, distribution and marketing based online by using applications on smartphones, in the form of Instagram, Whats App, smart cashiers and Canva. After the implementation of this program, it can increase knowledge and insight financial technology to 79 percent and skills using smartphone applications to 82 percent. Successful community service achievement makes partners more motivated to develop micro and small businesses. Further community service activities, need to be conducted continuously with various themes and increase the duration of the meeting.